2006
DOI: 10.1021/cm0522275
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Viability in Sol−Gel Materials Revisited:  Cryo-SEM as a Suitable Tool To Study the Structural Integrity of Encapsulated Bacteria

Abstract: Biocompatibility is an important issue that still needs research if one desires to fully preserve the metabolic activity of cells encapsulated in any type of material. Spectroscopic techniques (e.g., NMR and fluorescence) have been used to study the viability decrease upon aging time of bacteria encapsulated in silica gel materials. Unfortunately, none of these spectroscopic techniques are able to provide insights about the detrimental causes affecting the viability of encapsulated cells. The current work uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 39 publications
1
65
1
Order By: Relevance
“…In order to overcome this drawback, the authors explored other possibilities such as the incorporation of glycerol in the silica matrix to increase bacteria viability ( Figure 1.4C), leading to almost 50 % of viable bacteria after one month of ageing [63], or the addition of quorum sensing molecules involved in intercellular communication, which increase the cells viability to 100 % after one month [64]. Similar results have been achieved recently by Ferrer et al [65], who showed that gluconolactone-bearing organopolysiloxane matrices are more efficient than pure silica in extending E. coli the cells viability due to their increased biocompatibility (Figure 1.4D).…”
Section: Bio-nanohybrids Based On Silica Particles and Siloxane Networkmentioning
confidence: 52%
“…In order to overcome this drawback, the authors explored other possibilities such as the incorporation of glycerol in the silica matrix to increase bacteria viability ( Figure 1.4C), leading to almost 50 % of viable bacteria after one month of ageing [63], or the addition of quorum sensing molecules involved in intercellular communication, which increase the cells viability to 100 % after one month [64]. Similar results have been achieved recently by Ferrer et al [65], who showed that gluconolactone-bearing organopolysiloxane matrices are more efficient than pure silica in extending E. coli the cells viability due to their increased biocompatibility (Figure 1.4D).…”
Section: Bio-nanohybrids Based On Silica Particles and Siloxane Networkmentioning
confidence: 52%
“…Organopolysiloxane precursors bearing biocompatible groups such as gluconolactone seem also helpful for this purpose, producing a biocompatible matrix. 330 The aim of all these approaches is to produce robust biohybrid materials in which the viability of cells is guaranteed, showing a long-term stability. These properties are of major importance for the diverse areas of application.…”
Section: Silica and Silicate Biohybrids Incorporating Whole Cells Andmentioning
confidence: 99%
“…[77] The increased biocompatibility of gluconolactone-bearing organopolysiloxane matrices is more efficient than pure silica in extending the cell viability of Escherichia coli. [78] Alcohol added or released during the hydrolysis process of alkoxysilanes, the usually employed acid or base catalysts in sol-gel routes, as well as the excess sodium concentration and the high value of ionic strength as a result of the use of sodium silicate, can be harmful for most of biologicals. To overcome these drawbacks, alcohol-and catalyst-free routes that make use of a water-soluble ethylene glycol-containing precursor such as tetrakis(2-hydroxyethyl)orthosilicate (THEOS) [17c] or even the commonly employed alkoxysilanes (tetramethoxysilane (TMOS), methyltrimethoxysilane (MTMOS), etc.)…”
Section: Entrapment Of Biological Species Using Soft Networkmentioning
confidence: 99%